2010
DOI: 10.1021/ic100202h
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electronic Mixing in Ruthenium(II) Complexes with Two Equivalent Acceptor Ligands. Spectroscopic, Electrochemical, and Computational Studies

Abstract: The lowest energy metal to ligand charge transfer (MLCT) absorption bands found in ambient solutions of [Ru(NH(3))(4)(Y-py)(2)](2+) and [Ru(L)(2)(bpy)(2)](+) complexes (Y-py a pyridine ligand and (L)(n) a substituted acetonylacetonate, halide, am(m)ine, etc.) consist of two partly resolved absorption envelopes, MLCT(lo) and MLCT(hi). The lower energy absorption envelope, MLCT(lo), in these spectra has the larger amplitude for the bis-(Y-py) complexes, but the smaller amplitude for the bis-bpy the complexes. Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
77
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(86 citation statements)
references
References 76 publications
9
77
0
Order By: Relevance
“…The difference between the 300 K absorption and 77 K emission maxima of pentaammine− and tetraammine−Ru complexes (9.9 ± 0.5 and 7.6 ± 0.8 cm −1 /10 3 , respectively) is significantly larger than those found for the Ru−bpy chromophores (about 5−6 cm −1 / 10 3 ) 36 and about 30% larger for the pentaammines than for the other Ru−MDA complexes.…”
Section: ■ Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…The difference between the 300 K absorption and 77 K emission maxima of pentaammine− and tetraammine−Ru complexes (9.9 ± 0.5 and 7.6 ± 0.8 cm −1 /10 3 , respectively) is significantly larger than those found for the Ru−bpy chromophores (about 5−6 cm −1 / 10 3 ) 36 and about 30% larger for the pentaammines than for the other Ru−MDA complexes.…”
Section: ■ Introductionmentioning
confidence: 65%
“…Literature syntheses were used for the following compounds: [Ru(NH 3 ) 5 (L)] 2+ complexes with L = py, ac-py, ph-py, 4,4′-bipyridine (4,4′-bpy), and pyrazine (pz) and 17,33−35 cis-/trans-[Ru(NH 3 ) 4 (L) 2 ](PF 6 ) 2 with L = pz, py, ac-py, and ph-py ( Figure 1). 36 Table 1. prepared by dissolving the corresponding [Ru(NH 3 ) 5 (MDA)](PF 6 ) 2 complex in D 2 O and then precipitating it with the addition of saturated NaPF 6 /D 2 O solution. This procedure was repeated several times as described previously.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17][18] However, our recent work combining spectroscopic studies with density functional theory (DFT) modeling has found several excited state properties of ruthenium-(D)/polypyridyl ligand-(A) complex excited states that differ from expectation based on simple limiting models. [19][20][21][22][23][24] Thus, when the donor and 3 acceptor are covalently linked, and since the energy differences between excited states are often not large in heavy metal complexes, theoretical models based on such weak coupling limits can be misleading. 25 In the present paper we examine the 77 K radiative properties (spectra, quantum yields and lifetimes) of simple Ru-bpy complexes in order to gain more critical insight into the effects of electronic mixing on metal to ligand charge transfer (MLCT) excited state properties.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum MLCT wavelength in polypyridinic ruthenium compounds can be roughly estimated by the energy related to the oxidation of the metal and the first reduction of the ligands [21]. According to the electrochemical data the maximum MLCT wavelength for this complex should be observed at ca.…”
Section: Effect Of the Solution Ph On The Spectroscopic Propertiesmentioning
confidence: 98%